Livelihood Crisis and Distress Seasonal Migration: A Study of Beed District in Maharashtra - C. P, Abdul Jaleed; Chattopadhyay, Aparajita (National Geographical Journal of India, 2022)
Seasonal migration is widespread in rural central and eastern Maharashtra where agriculture is mainly rain-fed. Our study explores 350 seasonal migrant households that is defined as a household having, at least, one member who stayed away from the village for the purpose of employment for at least one month and not more than six months during the dry season. After sowing the Rabi Crops, villages face severe seasonal unemployment. To tide over the lean season, thousands of small and marginal peasant households migrate to other districts of the state, and even outside, in search of livelihood opportunities in sugar factories and brick kilns. Drawing connections between seasonal migration and rural crisis, our narrative shows how seasonal migration compensates for the lack of employment opportunities during the dry season and it reduces seasonal income variability of the poor households in Beed district.